Breaking the Silence: On Writing The Silent Predator - Júlíana Garðarsdóttir 1989- (2015)
This is a final assignment for a bachelor degree in English from the University of Iceland. It consists of two parts: first there is a novella called The Silent Predator (about 24,000 words) and then a report on the writing process (about 7,000 words). The Silent Predator is a supernatural thriller about an accomplished psychologist, Veronika Davis, who works in a forensic unit in a mental institution in Boston. She fears for her life when one of her patients is released, against her wishes, from the hospital. Soon afterwards, she starts experiencing odd events that she fails to explain with her usual tools: logic and reason. Veronika starts wondering whether she could be developing a mental illness or if she could be inheriting her mother’s early-onset Alzheimer’s disease. As she is trying to figure out whether she is actually being stalked or if she is hallucinating her experiences, she hides her concerns from the people in her life. Soon things get out of control and she confides in her brother, Jakob Davis. He starts digging around for answers and eventually discovers the startling truth behind what is really going on with his sister. The second part of this thesis, the exposition, is a report on the writing process of the novella. It describes how the story transformed from just an idea into a full novella. The exposition covers everything from how I got the idea for this story two years ago to the final editing process before submission. I trace the thought process behind the major decisions, describe the research required for this project, how the characters developed, discuss the role of the outline, talk about the obstacles I came across while writing the novella and the strategies I came up with for tackling them.